Dean Mosman letter to Nicholas S. Halmi regarding fall migration, 1976 - Mosman, Deanet al (1976)
Fall migration report contributed by Dean Mosman in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Fall 1976. Epson - sheet feed/flatbed